The Novel and the Common School - Warner, Charles Dudley, 1829-1900 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Novel and the Common School" by Charles Dudley Warner is an analytical treatise written in the late 19th century. This work explores the evolution of education in the United States, particularly focusing on the role of novels and literature within the common school system. Warner discusses how the intellectual development of the American populace is both a product and a reflection of the educational system, raising questions about the quality of literature that students encounter and how it shapes their tastes and intellectual capacities. In the text, Warner delves into the relationship between the common school and the literary tastes of the population, arguing that the prevalent reading habits fostered by public education often lean towards mediocre literature. He provides a critical examination of the kind of fiction that becomes popular, suggesting that it tends to cater to base sentiments rather than promote higher ideals or artistic value. Warner asserts that a more enriching literary exposure in educational settings would not only elevate individual taste but also nurture a more discerning and culturally enriched public, ultimately benefiting the quality of American literature and art. He believes that if schools can integrate superior literature into the curriculum, it will cultivate a more appreciative audience that demands and supports better literary works. (This is an automatically generated summary.)
Release date is 2004-12-05
Produced by David Widger
Keywords: Education -- United States